The application and optimization of super-resolution reconstruction for isotropic out-of-plane MRI to study the musculoskeletal system. Issue 4 (4th July 2021) - Tse, Justin J.; Garland, Luke; Kuczynski, Michael T.; Salat, Peter; Pauchard, Yves; Manske, Sarah L.
ABSTRACT: In this paper we optimised and adapted a post-processing super-resolution reconstruction (SRR) algorithm for its use in the semi-automated isotropic reconstruction of non-isotropically acquired musculoskeletal magnetic resonance image (MRI) data. The ability to produce isotropic MRI data facilitated the (1) enhanced out-of-plane image visualisation; (2) semi-automated image registration with CT data of the same anatomical site; and (3) improved image segmentation. The effectiveness of the SRR algorithm was demonstrated on several musculoskeletal scans including ex vivo tibial plateaus, in vivo knees and hands with varying levels of structural complexity and potential for motion artefact.